Hierarchy of Needs in Charlie’s Character in The Perks of Being a Wallflower - Azmi, Ahmad Nizam (Journal of Literature, Linguistics, & Cultural Studies, 2024)
As social beings, humans have a variety of needs that form the basis of their existence. Abraham Maslow (1943) categorized five hierarchies of needs consisting of physiological needs, safety needs, love and belonging needs, self-esteem needs, and self-actualization needs. In this study, researcher used the hierarchy of needs theory to analyze the main character in the novel The Perks of Being a Wallflower by Stephen Chbosky which aims to find out how Charlie fulfills his hierarchy of needs. This research uses a literary psychology approach by paying attention to the psychological aspects of the main character in the novel. Researcher collected data in the form of sentences, paragraphs, and dialog related to the hierarchy of needs. The results of this study show that the way Charlie fulfills the hierarchy of needs in Stephen Chbosky's The Perks of Being a Wallflower is through 5 elements. Physiological needs, the main character Charlie tries to fulfill his physiological needs in the form of eating and sleeping. Safety Needs, Charlie can fulfill the need for safety by forming a close friendship with Bill. Bill provides emotional support and psychological safety for him. Love needs, this need for love can be fulfilled by Charlie by forming close bonds with his new friends, such as Sam and Patrick. They give emotional support and make him feel accepted. Esteem needs, Charlie manages to fulfill his self-esteem needs in two ways: self-esteem needs from himself and self-esteem needs from others. Charlie manages to meet his self-actualization needs through his passion for reading, writing and literature.